Age at menarche among rural school youth in west-central Poland: variation with weight status and population growth - Bartkowiak, Sylwia; Konarski, Jan M.; Strzelczyk, Ryszard; Janowski, Jarosław; Karpowicz, Małgorzata; Malina, Robert M. (Anthropological Review, 2021)
Studies of age at menarche in Poland have a long history and consistently show an urban-rural gradient. The objectives of the study were to to estimate the age at menarche among school girls resident in ten rural communities of the Greater Poland province in 2016 and to compare ages at menarche by weight status and by population growth. The sample included 1146 girls, 7–16 years of age, resident in ten rural communities. Menarcheal status was obtained via interview. Heights and weights were measured; the BMI was calculated. Based on the latter, the girls were classified as thin, normal weight and overweight (including the obese) relative to IOTF criteria. Population growth between 1986 and 2016 in each community was estimated from local records. Ages at menarche were estimated with the probit regression protocol (SPSS) using the logistic model with log 10 transformation for the total sample and for the subsamples by weight status and population growth. The median age at menarche for the total sample of rural girls was 13.25±0.20 years. Menarche was earlier among Overweight (13.06±0.32 years) compared to Normal Weight (13.25±0.37 years) and Thin (13.81±0.41 years), and among girls resident in communities with Major population growth (12.58±0.44 years) compared to Little/No growth (13.65±0.14 years). Results of the present survey were generally consistent with recent surveys of age at menarche among rural girls in Poland and among girls classified by weight status. Corresponding comparative data relating menarche to population growth are lacking.